Biosynthesis of Methyl Esters from Used Cooking Oil (UCO) using Lipase Enzyme from Aspergillus oryzae on Moldy Copra - Dali, Nasriadi; Dali, Seniwati; Chairunnas, Armadi; Amalia, Hilda Ayu Melvi; Puspitasari, Ayu Andini (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
The successful production of methyl esters from used cooking oil (UCO) using lipase enzymes from Aspergillus oryzae on moldy copra has been achieved. This method offers an eco-friendly substitute for crude palm oil (CPO) in generating methyl esters or biodiesel, contributing to waste reduction, economic benefits, and lowered greenhouse gas emissions for sustainable development. This study aimed to synthesize methyl esters from UCO using the Aspergillus oryzae lipase enzyme sourced from moldy copra. The enzyme was purified through ammonium sulfate fractionation and gel filtration column chromatography. Electrophoresis validated its purity, and activity was assessed through the Erdmann and Lowry method. Methyl ester synthesis involved transesterification with a UCO (1 mol): methanol (9 mol): lipase enzyme (15% v/v) ratio. The enzyme displayed notable characteristics, including 43.76 units/mg protein activity, a 41.7 kDa molecular weight, optimum pH of 8.2, temperature preference of 35°C, Km of 0.046, and a 1.926 µmol/minute Vmax. This enzyme efficiently catalyzed UCO (triolein) into methyl ester (methyl oleate), yielding 75.65%. Characterization using Fourier Transform Infrared (FTIR) revealed specific functional groups like –OH carboxylic acid, C=C alkenes, C=O esters, methyl (CH3-), and methylene (-CH2-). Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified prominent compounds: methyl palmitate (12.53%), methyl vacsenate (16.44%), and, notably, methyl oleate (41.08%). This underscores the potential of Aspergillus oryzae lipase as an effective biocatalyst for UCO transesterification, yielding valuable methyl esters or biodiesel.